Difference in sucrose concentration between scion and rootstock influences the incompatibility of cucumber/pumpkin grafted plants - Chentong Guan; Yage Xu; Hongzhong Yue; Xinhui Qiao; Guangling Chen; Mingzhu Yuan; Yu Wang; Jin Sun (Horticultural Plant Journal)
Grafting is widely used in cucumbers to enhance their tolerance to environmental stress. Compatibility is a key factor for successful grafting, however, the physiological mechanisms that affect grafting compatibility are not clear. This study aimed to investigate the physiological mechanism underlying cucumber/pumpkin grafting compatibility. Two pumpkin cultivars with significant differences in compatibility, Figleaf gourd (compatible rootstock, Cf) and Dongyangshenli (incompatible rootstock, Cmo), were used as rootstocks. Three cucumber cultivars with different growth rates were used as scions, including cucumber ‘Shenluchunsi’ (strong growth, V1), ‘Cuilü’ (weak growth, V2), and ‘Liangyoulüjian 102’ (medium growth, V3). Six grafting combinations (V1/Cf, V2/Cf, V3/Cf, V1/Cmo, V2/Cmo, and V3/Cmo) were used to analyze the effect of scion and rootstock varieties, as well as the chemical composition of the exudate from the stem cutting surface, on the compatibility of grafted plants. Here, we found that rootstock was closely correlated with the compatibility of cucumber/pumpkin grafted plants. The sucrose content in the exudate of the stem, enzyme activity, and the expression of genes related to sucrose biosynthesis in Cmo were significantly higher than those in Cf. Correlation analysis showed that the sucrose content difference between the exudate of rootstock and scion stems was negatively correlated with graft compatibility. Exogenous treatment with a 0.5 % sucrose solution on the scions significantly reduced the difference in sucrose content between rootstock and scion and enhanced graft survival rate in the incompatible combination. The stem segment grafting experiment in vitro found that the high difference in sucrose concentration between the rootstock and scion decreased the grafting compatibility of cucumber/pumpkin by reducing the adhesion of the cutting surface. Taken together, the higher sucrose concentration difference between rootstock and scion decreased the adhesion of the cutting surface, resulting in the incompatibility of cucumber/pumpkin grafted plants.